Performance of steel slag in highway surface course - Hainin, Mohd. Rosli; A. Aziz, Md. Maniruzzaman; Shokri, Manouchehr; Putra Jaya, Ramadhansyah; Abdul Hassan, Norhidayah; Ahsan, Amimul (Penerbit Universiti Teknologi Malaysia, 2014)
As the quantity of disposing waste material is increasing in road construction, researchers are exploring the use of alternative materials which could preserve natural sources and save the environment. One of these sustainable materials is steel-furnace slag which is a synthetic aggregate produced as a consequence of the electric arc furnace (EAF). Steel slag was selected due to its characteristics, which are almost similar to conventional aggregates, and the fact that it is easily obtainable as a by-product from the steel industry. The same gradations of mixtures were produced using normal crushed aggregate as control samples. The experimental research has been articulated in a preliminary study of the chemical, leaching, physical, and mechanical properties of the electric arc furnace (EAF) steel slag. In addition, the outstanding benefits of steel slag were highlighted. All the mixtures with EAF steel slag have satisfied the requisites for acceptance in the road sector technical standards, thus resulting as suitable for use in the construction of road infrastructures.